Promotional tools toward marketing unit activities in UTM / Shahila Abd Razak - Abd Razak, Shahila (2010)
This research paper refer to the promotional tools that been examine marketing unit in UTM. The main unit handling marketing activities is University Marketing Unit in UTM but the other unit also doing some marketing activities. This research will investigate because of the decentralized marketing activities being implementing in UTM. The promotional tools being covers five technique are advertising, personal selling, sales promotion, public relation and direct marketing. This research will determine the hypothesis being made to predict the relationship of promotional tools being implemented by UTM marketing units. The first objective is to determine the level of promotional tools been implementing in marketing unit in UTM. The second objective is to determine the relationship between promotional tools towards UMU. The third objective is to identify the most influence tools towards promotional done by UMU. The last but not least objective is to identify the recommendation for UMU in enhancing the promotional activities in UTM. This research paper the nature of the research design into three divisions which is exploratory, descriptive and causal research. The exploratory research will be based on the problem statement and we can review on the literature review for the proof. The exploration based on any proof from journal that been explore from other people research. The descriptive research was based on the determination of objectives in this research and causal from the hypothesis. Population was 41 and the stratified sampling 37 respondent. The findings of this research show that the most influence tools implement by UTM is advertising. Beside that, other promotional tools like personal selling, public relation, sales promotion and direct marketing not really implement smoothly in UTM.